1974
DOI: 10.1073/pnas.71.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of the Sequential Release of Small and Large Molecules from Tumor Cells by Low Temperature During Cytolysis Mediated by Immune T-Cells or Complement

Abstract: Specific lysis of tumor cells by thymusderived lymphocytes from alloinmmunized mice (T-effector specific Iysis) was studied with target cells labeled with isotopes attached to both small ('4C-labeled nicotinamide) and large (5"Cr-labeled) molecules. The results confirm and extend previous reports that target cells release small molecules considerably earlier than large molecules during T-effector specific lysis. After interruption of T-effector specific lysis by specific antibody and complement directed agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…To address the second difficulty, we devised our experiments to compare chromium release from experimental plates to that from control cultures derived from the same umbilical cord. We have also attempted to address the inherent difficulties of using chromium release as a marker of cellular damage, including the facts that its leakage is usually indicative only of extensive membrane damage, and sublethal injury to cells frequently goes undetected (26). Thus, we utilized in ancillary studies, an unrelated cytotoxicity assay-that of fluorochromasia-to validate endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…To address the second difficulty, we devised our experiments to compare chromium release from experimental plates to that from control cultures derived from the same umbilical cord. We have also attempted to address the inherent difficulties of using chromium release as a marker of cellular damage, including the facts that its leakage is usually indicative only of extensive membrane damage, and sublethal injury to cells frequently goes undetected (26). Thus, we utilized in ancillary studies, an unrelated cytotoxicity assay-that of fluorochromasia-to validate endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…It had been assumed that chromium is complexed to macromolecular protein (Henney, 1973;Ferluga & Allison, 1974;Martz, Burakoff & Benacerraf, 1974;Steinitz & Weiss, 1975), but there was no clear data supporting this view, and at least two earlier reports that the chromium occurred as a small molecule (Ronai, 1969;Rajam & Jackson, 1958). It had been assumed that chromium is complexed to macromolecular protein (Henney, 1973;Ferluga & Allison, 1974;Martz, Burakoff & Benacerraf, 1974;Steinitz & Weiss, 1975), but there was no clear data supporting this view, and at least two earlier reports that the chromium occurred as a small molecule (Ronai, 1969;Rajam & Jackson, 1958).…”
Section: Assay Of Cell Death By Release Of Isotope Markers ( I ) Genementioning
confidence: 99%
“…First, lymphocytes can act on membranes directly to cause permeability increases without the participation of other target cell components. Thus, it seems plausible that the observed early increases in target cell permeability (3)(4)(5) represent primary damage to the membrane and are not the secondary consequence of cell injury elsewhere. Second, target cell membrane protein is not necessary for the lymphocyte-induced permeability increase.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological studies of the killing reactions have demonstrated that the cytolytic process is accompanied by a marked swelling of the dying cell (2). The study of target cells internally labeled with molecules of different sizes shows that the smaller molecules are released from the dying cell faster than those of high molecular weight (3)(4)(5). High concentrations of macromolecules have been shown to suppress the final release of 51Cr from the target cell (5,6), but the interpretation of these findings is controversial (7).…”
mentioning
confidence: 99%